Pathophysiology of Bronchiectasis - Keir, Holly R.; Chalmers, James D. (Seminars in Respiratory and Critical Care Medicine, 2021)
Bronchiectasis is a complex, heterogeneous disorder defined by both a radiological abnormality of permanent bronchial dilatation and a clinical syndrome. There are multiple underlying causes including severe infections, mycobacterial disease, autoimmune conditions, hypersensitivity disorders, and genetic conditions. The pathophysiology of disease is understood in terms of interdependent concepts of chronic infection, inflammation, impaired mucociliary clearance, and structural lung damage. Neutrophilic inflammation is characteristic of the disease, with elevated levels of harmful proteases such as neutrophil elastase associated with worse outcomes. Recent data show that neutrophil extracellular trap formation may be the key mechanism leading to protease release and severe bronchiectasis. Despite the dominant of neutrophilic disease, eosinophilic subtypes are recognized and may require specific treatments. Neutrophilic inflammation is associated with elevated bacterial loads and chronic infection with organisms such as Pseudomonas aeruginosa. Loss of diversity of the normal lung microbiota and dominance of proteobacteria such as Pseudomonas and Haemophilus are features of severe bronchiectasis and link to poor outcomes. Ciliary dysfunction is also a key feature, exemplified by the rare genetic syndrome of primary ciliary dyskinesia. Mucus symptoms arise through goblet cell hyperplasia and metaplasia and reduced ciliary function through dyskinesia and loss of ciliated cells. The contribution of chronic inflammation, infection, and mucus obstruction leads to progressive structural lung damage. The heterogeneity of the disease is the most challenging aspect of management. An understanding of the pathophysiology of disease and their biomarkers can help to guide personalized medicine approaches utilizing the concept of “treatable traits.”
Keywords: bronchiectasis; inflammation; airway infection; personalized medicine